The Effect of the Student Teams Achievement Division (STAD) Cooperative Learning Approach on Mathematics Learning Outcomes at SDN 6 Sokong - Hadi, Lalu Husnul; Taufik, M.; Fitriana, Maulida Arum (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The aim of this research is to determine the effect of the STAD (Student Teams Achievement Division) cooperative learning approach on the mathematics learning outcomes of grade 2 students at SDN 6 Sokong, Betumping Hamlet, Sokong Village, Tanjung District, North Lombok Regency. This type of research is quantitative with a one group pre-test and post-test design approach. This research consists of two variables, namely the independent variable and the dependent variable. The independent variable in this research is cooperative learning with the STAD (Student Teams Achievement Division) model. Meanwhile, the dependent variable is mathematics learning outcomes. The sample size was 25 students. The collection technique that researchers used was pre-test and post-test, pre-test to see students' initial abilities, while post-test was used to see the extent of students' development after treatment, with t-test analysis the research results showed that the approach The STAD (Student Teams Achievement Division) model of cooperative learning on learning outcomes has a significant influence. This is proven by the average pre-test score of 56.4%, while the average post-test score is 70.4%. Likewise, the calculation results obtained from t-count > from t-table or 8,573 > 0.496, thus it can be stated that the cooperative learning approach using the student teams achievement division (STAD) model has an influence on mathematics learning outcomes in addition material.